Exposure to Pesticides in Pregnant Women can Cause Reproductive Health Problems - Kurniyawan, Enggal Hadi; Widiyantari, Ni Made Galuh; Maula, Hayyu Rizqiatul; Wulandari, Rita; Nugroho, Ardanny Alfiananto; Pramastuti, Melinda Nur; Maharani, Elshinta Dika (Jurnal Bidan Mandiri, 2024)
The use of pesticides has excellent benefits in the agricultural sector. On the other hand, the use of pesticides is also known to have detrimental risks. Prolonged exposure to pesticides is directly related to the possibility of disorders of the female reproductive system. Disorders of the reproductive system health in women are disorders that can lead to infertility, cancer, congenital abnormalities, and several problems during pregnancy and after pregnancy. This study aimed to determine the impact of pesticide exposure on women's reproductive health in agricultural areas. The process of searching for journal articles is carried out in the literature reviews from 3 databases, namely ScienceDirect, PubMed, and Google Scholar, with publication between 2018-2022. Finally, ten articles were determined that matched the research criteria and could proceed to the analysis stage. Excessive exposure to pesticides in pregnant women can cause reproductive system problems and hurt the baby to be born. Nurses can provide comprehensive nursing care so that they can improve the level of public health. Nurses can actively offer health education and promotion regarding women's reproduction in agricultural areas.